Assembly of Lanthanide-Containing Tungstotellurates(VI): Syntheses, Structures, and Catalytic Properties - Li, Jie; Shang, Shuxia; Lin, Zhengguo; Yao, Zishuo; Zhen, Ni; Li, Zhen; Chi, Yingnan; Hu, Changwen (Frontiers in Chemistry, 2020)
Lanthanide (Ln)-containing polyoxometalates (POMs) have attracted particular attention owing to their structural diversity and potential applications in luminescence, magnetism, and catalysis. Herein, three types of Ln-containing tungstotellurates(VI) (Ln = Dy3+, Ho3+, Er3+, Tm3+, Yb3+ and Lu3+), dimeric (DMAH)n[H22-n{Ln(H2O)3[TeW17O61]}2]ꞏmH2O (abbreviated as Ln2Te2W34; DMAH+ = dimethylammonium), mono-substituted (DMAH)7Na2{H2Ln(H2O)4[TeW17O61]}ꞏmH2O (abbreviated as LnTeW17) and three-dimensional (3D) inorganic frameworks (DMAH)n{H3-nLn(H2O)4[TeW6O24]}ꞏmH2O (abbreviated as LnTeW6), have been synthesized by using simple metal salts and characterized by single-crystal X-ray diffraction and other routine techniques. Interestingly, the assembly of these POMs is pH-dependent. Using the same starting materials, Ln2Te2W34 were obtained at pH 1.7, where two Dawson-like monovacant [TeW17O61]14− are linked by two Ln3+ ions; mono-substituted Dawson-like LnTeW17 were isolated at pH 1.9; and 3D inorganic framework LnTeW6 based on Anderson-type [TeW6O24]6− were formed at pH 2.3. It is also found that the assembly of Ln-containing POMs depends on the type of Ln3+ ions. The three types of POMs can be prepared by using Ln3+ ions with relatively smaller ionic radius, such as Tb3+-Lu3+, while the use of Ln3+ ions (La3+-Eu3+) results in the formation of precipitation or TeW18O62 clusters. Furthermore, three LnTeW6 (Ln = Tb3+, Er3+, Lu3+) were used as Lewis acid catalysts for the cyanosilylation of benzaldehydes and their catalytic activity decreases with the decrease of Ln3+ ionic radius, giving the order: TbTeW6 > ErTeW6 > LuTeW6. Notably, TbTeW6 is stable to leaching and can be reused for five cycles without a significant loss of its activity.